(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2014)
Abstrak Artikel ini menghuraikan tentang sejarah perkembangan negeri Kelantan bermula dari zaman pra sejarah. Tumpuan diberi kepada peranan dan sumbangan Kesultanan Melayu Kelantan dalam pembangunan negeri. Tiga era pemerintahan yang menjadi fokus ialah era Sultan Long Yunus Ibni Almarhum Sultan Long Sulaiman (1762-1798), Sultan Muhamad 1V Ibni Almarhum Long Kundor, and Sultan Yahya Petra Ibni Almarhum Sultan Ibrahim (1975-1975). Abstract This article describes the historical development of Kelantan state in the prehistoric times. The focus is on the role and contribution of the Malay Sultanate of Kelantan state in the development of the state. Three era of focus are the era of Sultan Long Yunus Ibni Almarhum Sultan Long Sulaiman (1762-1798), Sultan Muhamad IV Ibni Almarhum Long Kundor, and Sultan Yahya Petra Ibni Almarhum Sultan Ibrahim (1975- 1975).